STRATEGI PEMASARAN SOSIAL YAYASAN SETARA MELALUI AKTIVASI MEDIA SOSIAL, SOSIALISASI ORANG TUA, REKRUTMEN RELAWAN, MAIN EVENT, DAN PENDAMPINGAN ANAK - Rizqo Yuhda Ilaina; Yanuar Luqman (Interaksi Online, 2026)
The Setara Foundation faced low brand awareness, which resulted in minimal community and volunteer participation. The communication strategy employed was based on the concept ofIntegrated Marketing Communication (IMC), brand awareness, and community participationto ensure the message was consistently received by the target audience. The campaign focusedon Instagram, TikTok, and offline activities such as roadshows, parent outreach, openrecruitment, child mentoring, and main events. The program's implementation results showedan increase in the Setara Foundation's visibility and community involvement in variousactivities. Instagram reached 3,540 followers and reached 225,600, while TikTok reached 311followers and reached 22,000. The open recruitment attracted 74 applicants and resulted in 40volunteers. Parental understanding increased from 32.6% to 78.3%, and the main event wasattended by 152 participants. These findings indicate that the IMC strategy effectivelyincreased community awareness, understanding, and participation of the Setara Foundation.